THE EFFECT OF INTELLIGENCE, MOTIVATION AND LEARNING STYLE TO GENDER DIFFERENCES IN SECOND LANGUAGE LEARNING - Ilyas Ilyas (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This research basically is a part of gender difference in language, but for specifically, this research more emphasize to present a brief overview of second language learning and then discuss the subject of gender differences related to the second language learning.Learning language especially second language is not easy. It needed and involve many things to achieve the success.To master the language.The motivation, intelligence, and learning style are the subjects that can influence the learners to achieve their goal in learning. Through this research, the researcher want to know whetherÂ the motivation, intelligence and learning style can influence the second language learning or cannot, and whether there are gender differencesÂ in second language learning or there are not. The findings of this research prove motivation, intelligence and learning style influence the ability the second language.